2016
DOI: 10.1111/sms.12664
|View full text |Cite
|
Sign up to set email alerts
|

Back pain prevalence in adolescent athletes

Abstract: The research aimed to investigate back pain (BP) prevalence in a large cohort of young athletes with respect to age, gender, and sport discipline. BP (within the last 7 days) was assessed with a face scale (face 1-2 = no pain; face 3-5 = pain) in 2116 athletes (m/f 61%/39%; 13.3 ± 1.7 years; 163.0 ± 11.8 cm; 52.6 ± 13.9 kg; 4.9 ± 2.7 training years; 8.4 ± 5.7 training h/week). Four different sports categories were devised (a: combat sports, b: game sports; c: explosive strength sport; d: endurance sport). Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 30 publications
(60 reference statements)
4
50
1
Order By: Relevance
“…We also found a relationship between age and back pain in elite athletes, findings that chime with those of Müller et al . [19], but we did not observe this relationship in the physically active control group. This finding could be explained by the relatively small age range of our control group respondents.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…We also found a relationship between age and back pain in elite athletes, findings that chime with those of Müller et al . [19], but we did not observe this relationship in the physically active control group. This finding could be explained by the relatively small age range of our control group respondents.…”
Section: Discussioncontrasting
confidence: 79%
“…Müller et al . [19] reported a mean point prevalence of back pain of 8% in a large cohort of young elite athletes (n = 2,116, mean age 13.3 years). However, the prevalence of back pain in adult athletes was not addressed.…”
Section: Introductionmentioning
confidence: 99%
“…weightlifting, wrestling, soccer, baseball, tennis, gymnastics) are considered risk factors [1][2][3][4]. The incidence of low back pain (LBP) in young athletes has been reported in several articles [2][3][4][5], and spondylolysis is a very common cause of LBP in young athletes [6]. One study reported that 47% of young athletes with LBP had spondylolysis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Back pain (point) prevalence in adolescent athletes is reported at a rate of 8–20%, with a relevant increase beginning around age 14 and featuring sport-specific differences (Schmidt et al, 2014; Müller et al, 2017). Consequently, back pain can be considered a relevant risk factor in the careers of young elite athletes.…”
Section: Introductionmentioning
confidence: 99%